PENGEMBANGAN MEDIA PEMBELAJARAN BUKU LIPAT INOVATIF (BUPATIF) BERBASIS POP-UP BOOK UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN BERCERITA SISWA KELAS III SEKOLAH DASAR - Caya, Ade Astuti; Akhir, Muhammad; Paida, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is development research which aims to produce Innovative Folded Book (Bupatif) learning media in Indonesian language subjects to increase the learning motivation and storytelling ability of class III students at SDN 182 Dannuang. The development model used refers to the ADDIE model which includes analysis, design, development, implementation and evaluation activities. The research results show: (1) the media produced is the Innovative Folding Book (Bupatif) learning media; (2) the Innovative Folding Book (Bupatif) learning media was declared feasible by media, language and material experts with an average percentage of 96% in the very feasible category (3) the Innovative Folding Book (Bupatif) learning media was declared practical based on the practicality observation sheet with category “very practical”; (4) Innovative Folding Book learning media (Bupatif) was declared effective in increasing students' learning motivation and storytelling ability at the media trial, observation sheet and questionnaire stage with the result of increasing learning motivation getting the "very high" category and increasing learning ability getting the category "Very good". There is a significant difference in learning motivation and the results of students' storytelling abilities before and after using the Innovative Folding Book (Bupatif) learning media. Thus, these findings confirm that the Innovative Folding Book learning media can be an effective alternative in increasing students' learning motivation and storytelling ability.